Gynura procumbens ethanol extract and its fractions inhibit Th1, Th2 and Th17 but induce Treg cells differentiation during atherosclerosis development - Manimegalai Manogaran; Vuanghao Lim; Doblin Sandai; Rafeezul Mohamed (Shahrekord University of Medical Sciences, 2021)
Introduction: Gynura procumbens (Lorr.) Merr. (GP) displays cardio-protective effect, which may hinder atherogenesis induced by oxidized low-density lipoprotein (oxLDL) and leukocytes. The current study was undertaken to elucidate the chemical constituents of GP ethanol extract and its aqueous, chloroform, ethyl acetate, and hexane fractions, and their effects on CD4+ T cell differentiation during atherogenesis. Methods: Initially, the bioactive constituents in GP ethanol extract and its fractions were analyzed using gas chromatography-mass spectrometry (GC-MS). Generated mouse bone marrow dendritic cells (BMDC) were loaded with oxLDL and GP ethanol extract and its fractions for 24 hours and co-cultured with mouse CD4+ T cells for 72 hours. For the determination of T-bet, GATA-3, RORγt, Foxp3, DLL-3, and Jagged-1 mRNA gene expression, the floating cells (CD4+ T cells) and adherence cells (BMDC) were isolated from their total RNAs and reverse transcribed into cDNA.Results: GC-MS analysis showed that GP ethanol extract and its fractions contained various volatile compounds. GP ethanol extract and its fractions also increased the DLL-3 gene but suppressed Jagged-1 gene expression in oxLDL-treated BMDC. Furthermore, GP ethanol extract and its fractions suppressed T-bet, GATA-3, and RORγt gene expression but increased the expression of the Foxp3 gene in differentiated CD4 + T cells. Conclusion: GP ethanol extract and its fractions are composed of various bioactive chemical components that can induce anti-atherogenic effects by inhibiting pro-atherogenic cells such as Th1, Th2, and Th17 cells while increasing anti-atherogenic cells, Treg cells.